Effect of in vitro simulated gastro-duodenal digestion on the antioxidant and anti-inflammatory activity of South Africa Fynbos honey - Bester, Megan J. (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.